Futures and Beyond Creativity and 4IR Conference 2022 - Halligey, Alexandra (UJ Press, 2023)
The Futures and Beyond: Creativity and 4IR Virtual Conference was hosted online by UJ Arts & Culture on the 30th and 31st August, 2022. The University of Johannesburg has positioned the Fourth Industrial Revolution (4IR) as its visionary focus in research and higher education and UJ Arts & Culture, as a division of the Faculty of Art, Design & Architecture has been facilitating an ongoing discussion on how thinking around the notion of the 4IR connects to the creative industries. The Futures and Beyond Conference was an entirely new initiative coming out of this ongoing discussion. The thematic approach to the conference was divided into two streams, with one being ethics, intellectual property and technology and the other being creative industries, innovation and development.